At the intersection of language, logic, and information : ESSLLI 2018 Students Session, Sofia, Bulgaria, August 6-17, 2018. Selected papers /: ESSLLI 2018 Students Session, Sofia, Bulgaria, August 6-17, 2018. Selected papers. ([2019]) - Unknown
No abstract available